The Correlation between Lymphocyte Platelet Ratio and Gensini Score in Coronary Heart Disease Patients - Muliana Muliana; Basuki Rahmat; Seto Priyambodo (Universitas Muhammadiyah Yogyakarta, 2020)
The lymphocyte platelet ratio (LPR) is an inflammatory marker that can be used to identify the severity of coronary heart disease (CHD). This study aims to determine the correlation between the lymphocyte platelet ratio and Gensini scores in CHD patients. This research used correlative analytical research with a cross-sectional design. The sample was selected by consecutive sampling technique and obtained 51 respondents. The calculation of the LPR was carried out by dividing the number of platelets and lymphocytes in the volume unit of 103/mm3. Meanwhile, the Gensini score assessment was carried out by multiplying the percentage of blockages and location of blockages based on the result of coronary angiography. Based on the Gensini score, the sample in this study was classified as mild atherosclerosis with the Gensini score 25 points, and severe atherosclerosis with the Gensini score ≥25 points. The data were analyzed using the Pearson correlation test. The result showed that the average LPR value in samples with severe atherosclerosis was 124.6 and 115.3 in mild atherosclerosis. Based on the result of statistical analysis using the Pearson test, the p-value was 0.107. It can be concluded that there is no significant correlation between the lymphocyte platelet ratio and Gensini scores in CHD patients.